Pedicled flap transfer after chest wall malignant tumor resection and potential risk of postoperative respiratory problems for patients with low FEV1.0% - Asanuma, Kunihiro; Tsujii, Masaya; Hagi, Tomohito; Nakamura, Tomoki; Uchiyama, Teruya; Adachi, Ryohei; Nakata, Kenta; Kataoka, Takeshi; Sudo, Akihiro (Frontiers in Surgery, 2024)
Introduction Musculoskeletal transfer for chest wall tissue defects is a crucial method, and pedicled flaps around the chest wall are preferred in terms of location and simplicity of transfer. These require special care because of complications such as partial necrosis, fistula, wound dehiscence, infection, hematoma and restricted function of the arm or shoulder. However, studies of respiratory function are rare. In the present study, we investigated the complications including respiratory problems after wide resection for malignant chest wall tumors with musculoskeletal pedicle transfer. Methods A total of 13 patients (15 operations) who underwent wide resection of primary, recurrent, or metastatic malignant chest wall tumors and musculoskeletal pedicle transfer for coverage of tissue defects were enrolled in the present study. A retrospective review of all patients was performed using data collected from hospital records and follow-up information. The complications of musculoskeletal transfer after chest wall wide resection, including respiratory problems, are evaluated. Results Rib or sternal resection was performed in 12 operations, and only soft tissue resection was performed in 3 operations. Latissimus dorsi (LD) pedicle transfer was performed in 13 operations, and pectoralis major (PM) pedicle transfer was performed in 2 operations; basically, wounds were closed primarily. Surgical complications were observed following 5 of the 15 operations (33.3%). Respiratory complications were seen in 7 of the 15 operations (46.7%). Patients with respiratory complications showed significantly lower preoperative FEV1.0% values than those without respiratory complications (p=0.0196). Skin resection area tended to be higher in the complication group than in the no complication group (p=0.104). Discussion Pedicled myocutaneous flap transfers such as LD, PM, and rectus abdominus can be used following multiple resections. After harvesting LD or PM, the wound can be closed primarily for an 8 to 10-cm skin defect in patients with normal respiratory function. However, for patients with low FEV1.0%, after primary closure of LD or PM transfer for wide soft tissue defects, attention should be paid to postoperative respiratory complications.